Influência de porta-enxertos nas características físico-químicas do mosto e dos vinhos bordô, isabel e IAC 138-22 máximo - Silva, Marlon Jocimar Rodrigues Da [UNESP]; Brunelli, Luciana Trevisan [UNESP]; Moura, Mara Fernandes; Hernandes, José Luiz; Leonel, Sarita [UNESP]; Tecchio, Marco Antonio [UNESP] (FapUNIFESP (SciELO), 2017)
It has been demonstrated that rootstocks can influence grape characteristics, but there are few data in literature about the rootstocks influence in the wine characteristics, especially in wines elaborated with Vitis labrusca or hybrid grapes. This study evaluated the influence of ‘IAC 766' and '106-8 Mgt’ rootstocks on the physicochemical characteristics of ‘Bordô', ‘Isabel’ and ‘IAC 138-22 ‘Máximo’ musts and wines. The musts were evaluated for pH, soluble solids, total acidity and soluble solids/acidity ratio. The wines were evaluated for density, alcohol content; total, volatile and fixed acidity; pH, dry extract, reducing sugars, reduced dry extract, alcohol in weight/reduced dry extract; free and total sulfur dioxide; anthocyanins, polyphenols index (I 280); polyphenols and total flavonoids and antioxidant activity. The ‘Bordô', ‘Isabel’ and IAC 138-22 ‘Máximo’ musts had low soluble solids for winemaking. The '106-8 Mgt’ rootstock promoted higher dry extract content and reduced dry extract in Bordô wine, and lower total and fixed acidity in IAC 138-22 Máximo wine. In Isabel wine, higher pH was promoted by the ‘IAC 766' rootstock. Aside from low total acidity of the Bordô wine, all the physicochemical characteristics of the wines studied are in accordance with Brazilian law. There was no effect of rootstocks in the phenolics content and antioxidant activity of wines.
Rootstocks effects on the physicochemical characteristics of bordô, Isabel and Iac 138-22 Máximo must and wine
Keywords: Antioxidant activity; Classical analysis; Phenolic compounds; Table wine; Vitis sp.